(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Ergonomics is the science that helps humans build machines or equipment. The application of ergonomics will give the individual satisfaction and comfort of living the community. Resilience is a person’s ability to react in a healthy and productive manner on petanque throw skills among slow learner students. The ergonomic is a branch of biomechanics practiced in sport as an external feature that involves the comfort of athletes. The comfortable training environment has impact on the performance of athletes. The purpose of this paper was to analyze the effect of ergonomic on petanque throw skill among slow learner students through an experimental approach. This type of study was a quasi-experiment utilizing descriptive quantitative methods. Data were collected from 16 slow learner students by using pre-test and post-test. The test score form was used as an instrument in this study. Data obtained were analyzed through the Statistical Package for Social Science (SPSS) version 22.0. The findings showed that there were no significant differences between pre-test and post-test on weight of ball (t = -1.414, p > 0.05) and on colour of ball (t = 1.000, p > 0.05). The findings showed that there were significant differences between pre-test and post-test by distance of game area (t = 2.530, p <0.05). This study will provide guidance to teachers in improving petanque throw skill among slow learner students.